The Importance Of SMEs In Turkey For Macroeconomic Sustainability and Increasing Competitiveness Power - Erdil Şahin, Begüm (My University, 2015)
Small and Medium Scale Enterprises (SMEs) are the leading and dynamic elements of the economy in Turkey, as is the case throughout the world. They have an important position in terms of socio-economic development. Moreover, they undertake important functions as a tool for the protection of competition, development of entrepreneurship, creation of jobs and regional development. They also support and complement the large industrial organizations. Under the rapidly developing and changing market conditions, SMEs are very important in terms of the value they contribute to the economy and they play a key role in the enhancement of competitive powers of the countries as well as their development. The competition rising with the globalization makes technological innovation necessary for the enterprises. Moreover, in developing countries like Turkey, the presence of large scale enterprises with high competitive power also depends on the creation of a structure of dynamic and stabile small and medium scale enterprises. The purpose of this study is to evaluate the importance of SMEs in Turkey for macroeconomic sustainability, technology and R&D in terms of competitiveness of SMEs, and the problems regarding R&D activities as well as the support policies implemented in Turkey to enhance competitive power.
Keywords: Small and Medium Enterprises (SME); R&D; Competitiveness; Macroeconomic Sustainability; Turkey